Increasing roughness of the human breast cancer cell membrane through incorporation of gold nanoparticles - Lara-Cruz, C (Int J Nanomedicine, 2016)
Gold nanoparticles (AuNPs) have been proposed for use in the treatment of different types of cancer, including breast cancer. At present, neither the mechanisms of AuNP interaction with the plasma membrane surface and their delivery and intracellular distribution in cancer cells nor their effect on the plasma membrane so as to allow cell incorporation of larger amounts of AuNPs is known. The objective of this work was to study the interaction of bare 20 nm diameter AuNPs with the plasma membrane of human MCF-7 breast cancer cells, as well as their uptake, intracellular distribution, and induction of changes on the cell surface roughness. The dynamics of intracellular incorporation and the distribution of AuNPs were observed by confocal laser scanning microscopy. Changes in roughness were monitored in synchronized MCF-7 cells by atomic force microscopy high-resolution imaging at 6 hour intervals for 24 hours during a single cell cycle. The results show that bare AuNPs are capable of emitting fluorescence at 626 nm, without the need for a fluorescent biomarker, which allows monitoring their uptake and intracellular distribution until they reach the nucleus. These results are correlated with changes in cell roughness, which significantly increases at 12 hours of incubation with AuNPs, when compared with control cells. The obtained data provide bases to understand molecular processes of the use of AuNPs in the treatment of different diseases, mainly breast cancer.